(untitled) (Singaporean Journal of Business Economics and Management, 2015)
The politics and Social-legal instruments of regional merger schemes or world Government were aimed ultimately at achieving supra-nationalism (aka a complete political union) beyond that of the five tenets of economic integration by a group of acceding sovereign (independent) States within a contiguous geographical zone or geo-strategic zones. A typical example was found in the European Union (EU) which was aimed at providing a common national identity, external common defense and national security, securing of a larger inter-continental market for its agricultural products, consumer goods and industrial raw materials availability and affordability as vital factors input within the mega zone. Politically, the sole goal of a world Government was to actualize a balance of power and octopus superpower status hitherto unattainable by smaller states within the zone. Mergers represent a comity of nations by fusion with stronger bargaining power in global political equations and economic trade negotiations. This paper examined how achievable were these goals in the Economic Community of West African States (ECOWAS) in this 21st century as other trading blocs across the globe grapple with the harmonization and challenges of social-legal instruments at each tenet stage of merger schemes, using Nigeria and the ECOWAS experiences as the probe-focus of analysis.